Clinical progression, pathological characteristics, and radiological findings in children with diffuse leptomeningeal glioneuronal tumors: A systematic review - Jiang, Haoxiang; Qiu, Lu; Song, Juan; Xu, Dandan; Sun, Lei; Feng, Yinbo; Zhao, Jun; Qian, Jun; Yu, Zhiwei; Peng, Jin (Frontiers in Oncology, 2022)
Background Diffuse leptomeningeal glioneuronal tumors are rare leptomeningeal neoplasms composed of oligodendrocyte-like cells characterized by neuronal differentiation and a lack of isocitrate dehydrogenase gene mutation. Purpose We aimed to analyze the clinical progression, pathological characteristics, and radiological findings of diffuse leptomeningeal glioneuronal tumors in children, as well as the relevance of clinico-radiological data. Data Sources We searched MEDLINE, PubMed, and Web of Science to identify case reports, original articles, and review articles discussing diffuse leptomeningeal glioneuronal tumors published between 2000 and 2021. Study Selection The analysis included 145 pediatric patients from 43 previous studies. Data Analysis Data regarding patient pathology, MRI manifestations, clinical symptoms, and progression were collected. The relationship between imaging classification and pathological findings was using chi-square tests. Overall survival was analyzed using Kaplan–Meier curves. Data Synthesis Parenchymal tumors were mainly located in the intramedullary areas of the cervical and thoracic spine, and patients which such tumors were prone to 1p-deletion (χ2 = 4.77, p=0.03) and KIAA1549-BRAF fusion (χ2 = 12.17, p<0.001). The median survival time was 173 months, and the survival curve fell significantly before 72 months. Parenchymal tumor location was associated with overall survival (p=0.03), patients with KIAA 1549-BRAF (+) and treated with chemotherapy exhibited a better clinical course (p<0.001). Limitations The analysis included case reports rather than consecutively treated patients due to the rarity of diffuse leptomeningeal glioneuronal tumors, which may have introduced a bias. Conclusions Early integration of clinical, pathological, and radiological findings is necessary for appropriate management of this tumor, as this may enable early treatment and improve prognosis.